Determination of the New SNP g.939A>G of the TYR Gene in Abnormal Coat Color in Bali Cattle - Kholijah; Mokhmad Fakhrul Ulum; Sri Darwati; Ronny Rachman Noor; Jakaria (Faculty of Animal Science, Universitas Brawijaya, 2024)
This study aimed to assess the presence of single nucleotide polymorphisms (SNPs) in the exon 1 region of the tyrosinase (TYR) gene in Bali cattle with abnormal coat color. This study analyzed 43 Bali cattle, 26 individuals with typical or standard coat color, and 17 individuals with albinism. The genetic diversity of the TYR gene was determined via direct sequencing and polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) techniques. The sequence data of the TYR gene were scrutinized using BioEdit and MEGA10 software to detect single nucleotide polymorphisms (SNPs) related to different types of coat color features in Bali cattle. The genetic diversity information was derived from computations performed using PopGen 1.32 software. The results showed that exon 1 of the TYR gene was affected by the new SNP g.939A>G, which is polymorphic in Bali cattle. In conclusion, the SNP c.939A>G can be further analyzed for use as a candidate-assisted selection (MAS) for abnormal coat color in Bali cattle.